EVALUASI SIFAT FISIK SEDIAAN SHAMPO EKSTRAK DAUN KATUK (Sauropus androgynus (L) Merr) DENGAN BERBAGAI VARIASI VISCOSITY AGENT - Rashati, Dewi; Eryani, Mikhania Christiningtyas (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
Sauropus androgynus (L) Merr leaf in Indonesia called katuk have strong antioxidant activity with IC50 80,01 ppm. The aims of this research is want to know physical properties of katuk leaf shampo which is formulated in various formulas. In this research katuk was formulated in shampoo with viscocity agent (HPMC, sodium CMC and Carbopol) in various concentration. The result showed that all shampoo formulas had low jasmine smell, but had different in form and colour. Shampoo viscocity increased with increased viscocity agent. The highest viscocity showed by F7 with 0,5% carbopol concentration. pH test showed that the shampoo with HPMC and sodium CMC had pH value 6. pH value of shampoo with carbopol was 5. All of pH formulas meet the requirement of SNI standard. Statistical result showed that the physical properties of foam high, viscocity and pH all formulas had significant difference.